1974
DOI: 10.1159/000260093
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Uptake and Caries Inhibition from Self-Application of an Acidulated-Phosphate-Fluoride Prophylaxis Paste

Abstract: The anti-caries effect of semi-annual self-applications of an acidulated-phosphate-fluoride prophylaxis paste to the teeth of children living in non-fluoridated areas was studied. Analysis of exfoliated deciduous teeth revealed an increase in enamel fluoride concentration of 120 ppm at 5 μm in anterior teeth and 15–35 ppm in posterior teeth after each application. The acquired fluoride did not increase with further applications but instead was lost within six months. Clinical examinations revealed 21% fewer DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Chewing 1 APF tablet every school day gave a 30-month reducton in DMFS increment of about 27% . A somewhat higher percentage caries reduction (37%) has been reported from tests with single annual appli cations of an APF gel [Bryan and Williams, 1970], APF gels (1.23 ppm F, pH 3) used for self-application 4-5 times per year by schoolchildren resulted in 19-24% DMFS reductions after 3 years [Trubman and Crellin, 1973;Horowitz et al, 1974], while slightly better results were reported by Mellberg et al [1974] and poorer results by Hei fetz et al [1970]. Brudevold and McCann [1968] were probably the first to stress the importance of the recrystallization-and remineraliza tion-enhancing effect of F ions, which is de pendent on the concentrations of all apatiteconstituting ions in plaque and saliva.…”
Section: Hydrogen Ion Concentrationmentioning
confidence: 87%
“…Chewing 1 APF tablet every school day gave a 30-month reducton in DMFS increment of about 27% . A somewhat higher percentage caries reduction (37%) has been reported from tests with single annual appli cations of an APF gel [Bryan and Williams, 1970], APF gels (1.23 ppm F, pH 3) used for self-application 4-5 times per year by schoolchildren resulted in 19-24% DMFS reductions after 3 years [Trubman and Crellin, 1973;Horowitz et al, 1974], while slightly better results were reported by Mellberg et al [1974] and poorer results by Hei fetz et al [1970]. Brudevold and McCann [1968] were probably the first to stress the importance of the recrystallization-and remineraliza tion-enhancing effect of F ions, which is de pendent on the concentrations of all apatiteconstituting ions in plaque and saliva.…”
Section: Hydrogen Ion Concentrationmentioning
confidence: 87%